Bright multiplexed source of indistinguishable single photons with tunable GHz-bandwidth at room temperature. (29th July 2021) - Davidson, O; Finkelstein, R; Poem, E; Firstenberg, O
Abstract: Narrowband single photons that couple well to atomic ensembles could prove essential for future quantum networks, but the efficient generation of such photons remains an outstanding challenge. We realize a spatially-multiplexed heralded source of single photons that are inherently compatible with the commonly employed D2 line of rubidium. Our source is based on four-wave mixing in hot rubidium vapor, requiring no laser cooling or optical cavities, and generates single photons with high rate and low noise. We use Hong–Ou–Mandel interference to verify the indistinguishability of the photons generated in two different (multiplexed) channels. We further demonstrate a five-fold tunability of the photons' temporal width. The experimental results are well reproduced by a theoretical model.